Univariate Artificial Neural Network In Forcasting Demand Of Low Cost House In Petaling Jaya - Bakhary, Norhisham; Yahya, Khairulzan; Ng Chin, Nam (Penerbit UTM Press, 2004)
Recently researchers have found the potential applications of Artificial Neural Network (ANN) in various fields in civil engineering. Many attempts to apply ANN as a forecasting tool has been successful. This paper highlighted the application of Time Series Univariate Neural Network in forecasting the demand of low cost house in Petaling Jaya district, Selangor, using historical data ranging from February 1996 to April 2000. Several cases of training and testing were conducted to obtain the best neural network model. The lowest Root Mean Square Error (RMSE) obtained for validation step is 0.560 and Mean Absolute Percentage Error (MAPE) is 8.880 %. These results show that ANN is able to provide reliable result in term of forecasting the housing demand based on previous housing demand record.